Efficacy of lenalidomide in POEMS syndrome: A retrospective study of 20 patients. Issue 3 (18th January 2013) - Royer, Bruno; Merlusca, Lavinia; Abraham, Julie; Musset, Lucile; Haroche, Julien; Choquet, Sylvain; Leleu, Xavier; Sebban, Catherine; Decaux, Olivier; Galicier, Lionel; Roussel, Muriel; Recher, Christian; et al.
<x xml:space="preserve">Abstract</x> POEMS syndrome is a rare disorder characterized by polyneuropathy, monoclonal gammopathy, multiorgan involvement, and elevated vascular endothelial growth factor levels. Localized bone lesions require irradiation, whereas young patients with disseminated disease receive intensive treatment with stem cell support. Treatment of older and non responding patients is not yet standardized. We report the use of a combination of lenalidomide and dexamethasone in 20 patients with POEMS syndrome. Four patients were newly diagnosed, and 16 had relapsed or progressed after treatment. All but one of the patients responded: clinical improvements were noted in neuropathies (16/20) organomegaly (13/13), peripheral edema (14/15), and pulmonary hypertension (5/5). At least a very good partial response was noted in 68% of patients, with partial responses in 26%. Serum VEGF levels fell markedly in all 17 patients with available values. Twelve patients had 18‐FDG‐PET/CT at diagnosis (11 with positive findings), and nine patients during follow‐up. The number of lesions fell markedly in five cases and remained stable in two cases, while two patients became negative. During a median follow‐up of 22 months, four patients relapsed. Toxicity, predominantly hematological, was mild and manageable. Lenalidomide thus appears to be effective in POEMS syndrome, inducing high rate of clinical and biological responses. Am. J. Hematol. 88:207–212, 2013. © 2012 Wiley Periodicals, Inc.